How to Assess and Prevent Risk of Diabetic Foot Ulcer - Pratama, Kharisma; Wuriani, Wuriani; Jiu, Cau Kim; Amrullah, Syahid; Pradika, Jaka; Lukita, Yenni; Usman, Usman; Hartono, Hartono; Erwhani, Indri (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
The discovery of problems related to health status was the beginning of the idea to carry out activities with the basic theme